Green Technology Monitoring System for Oyster Mushrooms - Ta'ahal, Siti Sri Noraini; Masek, Alias; Yusof, Yusmarwati (Research and Innovation in Technical and Vocational Education and Training, 2022)
The use of IoT technology in modern agriculture is growing rapidly, especially in the agricultural sector. The agricultural sector, especially oyster mushroom crops, faces the problem of supply sources, namely soaring electricity bills when they want to apply technology system in oyster mushroom house because several things that need to be ambient control which is humidity and temperature in the mushroom house. The project was developed to design an automatic ambient temperature control system of oyster mushroom house and develop a mushroom house power supply system using photovoltaic (PV) solar energy. Next, test the functionality of an automatic temperature control system using photovoltaic (PV) solar energy in the mushroom house. This Oyster Mushroom Care Monitoring Green Technology System uses a DHT22 sensor to detect humidity and ambient temperature in the mushroom house and an ultrasonic sensor to detect the water tank level. The system operates when the DHT22 sensor detects a temperature above 30˚C or a humidity of less than 70%, then a 12V DC water pump act to drip water onto the body of the mushroom chunk. Programming uses an Arduino with the C language, uses the NodeMCU ESP8266 as a microcontroller and sends temperature, humidity and water tank level data to the Blynk application. For the supply source using 25W solar panel, 12V 7.0Ah battery, 10A solar controller and 12V inverter to accommodate the system that uses power of 3.75Wh. Overall, this system is able to operate with solar energy supply well and facilitate the work of monitoring condition in the mushroom house.